The role of perinatal protection of a fetus in preservation of the health of the nation - Oleg V. Zavyalov; Irina V. Ignatko; Aleksander N. Strizhakov; Igor N. Pasechnik; Madina A. Kardanova (Педиатрическая фармакология, 2023)
This review examines the international role of perinatal protection of a fetus in preservation of the health of the nation. Historical perspectives, present-day developments, and future priorities of perinatal medical science are given. The etiology of decompensated placental insufficiency and intrauterine growth restriction is considered. The authors also considered the epidemiology of premature delivery and perinatal outcomes, the problem of development, diagnosis and obstetric management in critical fetal condition is covered in detail. The current review of literature was conducted in order to advance the theoretical knowledge of specialists on modern complex issues of perinatal medicine. The considered practical aspects will contribute to the improvement of interdisciplinary interaction between clinicians of various specialties in the field of perinatal protection of a fetus and, through this, to the preservation of the health of the nation and the multiplication of future generations.